Digital storage oscilloscopes - Hickman, Ian.; ScienceDirect eBooks (Oxford ; Boston : Newnes, 1997)
Digital storage oscilloscopes have long since completely supplanted analog storage oscilloscopes and have reached a degree of sophistication and performance which enable them to rival the most advanced real time oscilloscopes. In this comprehensive handbook, which provides a practical vade mecum for the engineer, Ian Hickman describes how they work and how to use them to best advantage. A wide range of models is available. This book includes a guide to all makes and models and will be best kept beside the instrument for instant reference. It will also be a most helpful guide to the subject for students and trainees. Ian Hickman is an experienced designer and author of best-selling titles including 'Oscilloscopes: How to Use Them, How They Work', Newnes Practical Radio Frequency Handbook', 'Analog Electronics' and 'Analog Circuits Cookbook'.
Introduction, Digital storage oscilloscope fundamentals; Digital storage oscilloscope modes of operation; Input circuitry; Digitising; Triggering; Signal processing; Displays and display technology; Digital sampling oscilloscopes; Accessories for use with digital storage oscilloscopes; Using digital storage oscilloscopes; Glossary; Appendix: Manufacturers of digital storage oscilloscopes and their agents; Index.
Print version record.
Safari Books Online
Elsevier
Keywords: Digital oscilloscopes; TECHNOLOGY & ENGINEERING -- Electronics -- Circuits -- Integrated; TECHNOLOGY & ENGINEERING -- Electronics -- Circuits -- General; Digital oscilloscopes; Electronic books